SOCIOLOGY OF SPORT - Sage, George Harvey; Eitzen, D. Stanley; Beal, Becky; Atencio, Matthew, 1975- (Oxford University Press, 2023)
"Now in its twelfth edition, Sociology of Sport offers a compact yet comprehensive and integrated perspective on sport in North American society. Bringing a unique viewpoint to the subject, George H. Sage, D. Stanley Eitzen, Becky Beal, and Matthew Atencio analyze and, in turn, demythologize sport. This method promotes an understanding of how a sociological perspective differs from commonsense perceptions about sport and society, helping students to understand sport in a new way"--